-4(3x+6y)+12x+4y=

Simple and best practice solution for -4(3x+6y)+12x+4y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3x+6y)+12x+4y= equation:


Simplifying
-4(3x + 6y) + 12x + 4y = 0
(3x * -4 + 6y * -4) + 12x + 4y = 0
(-12x + -24y) + 12x + 4y = 0

Reorder the terms:
-12x + 12x + -24y + 4y = 0

Combine like terms: -12x + 12x = 0
0 + -24y + 4y = 0
-24y + 4y = 0

Combine like terms: -24y + 4y = -20y
-20y = 0

Solving
-20y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-20'.
y = 0.0

Simplifying
y = 0.0

See similar equations:

| 12x+.50y=112 | | 3cotx+3=8 | | 0=-15-3y+2x | | 25=x+2x+3x+1 | | z^2-6z+9+2i=0 | | (X-y)+2x+y=11+19 | | 10r^2-21=-4R+6 | | 3cot+3=8 | | 4x-72=9x-18 | | 15+6c+c-8=16c+17-9c-10 | | 2x+8x^2=18 | | 5-6x-y=0 | | 0.08(15)+0.4x=0.05(36+7x) | | Y=-5-5x | | 4x-8=4r+8 | | 2+2y=5x | | 7n+4+n-4+2n=180 | | 2x-3[x+5(x-2)]= | | 4x+2x+3y-y= | | -8=-2y-x | | 11x-(3x-11)=6+7x | | x-.125x=1.5 | | l=200/520 | | -8=-6d-20 | | 12=-7x-3y | | 3x+15=2x+(4x-6) | | 7(8x-7)= | | 4t^2-9t+16=15-4t | | 15*2X=60 | | x-.125x=4.75 | | 4y=-3x+20 | | 5/3x=20/24 |

Equations solver categories